Pemberdayaan Kader Stuntcare (Reproduksi Ideal dan Anti Stunting pada Calon Pengantin) - Risqi Dewi Aisyah; Suparni Suparni; Aslam Fatkhudin; Velita Baiti Yantari; Nurul Azizah; M. Adil Hakim (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Stunting has long-term impacts on a child's growth, development, and overall quality of life. Prevention efforts starting from the preconception phase, particularly among prospective brides and grooms (catin), represent a strategic approach to breaking the cycle of stunting. This community service program aimed to strengthen the capacity of health cadres in educating and conducting early detection of stunting risks among catin. The program was conducted over eight months (May–December 2025) using an empowerment approach through focus group discussions, socialization, training, and mentoring activities. A total of 15 participants were involved, consisting of 12 cadres from Kranji Village and 3 health personnel from the local health center. Results showed an increase in the average knowledge score of cadres across three main topics: Ideal Reproductive Health for Catin by 6.2 points, Stunting Concepts (Detection and Prevention) by 5.14 points, and Nutrition for Catin by 2.67 points. These findings indicate that empowerment-based interventions are effective in forming cadres capable of playing an active role in stunting prevention starting from the preconception phase.